Dari Masjid ke Kafe: Kontestasi dan Modifikasi Budaya Dakwah Baru Melalui Penerapan Teknologi Broadcasting dan Penyiaran Konten - Zulkarnaen, Andi Achmad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Islamic preaching (dakwah) in Indonesia has undergone significant transformation with the emergence of new preaching models that extend beyond traditional mosque settings into public spaces such as cafés and digital platforms. This study aims to examine contemporary dakwah phenomena through the application of broadcasting technologies—including digital television, live streaming, podcasts, and social media—and to analyze the dynamics of contestation and cultural modification that arise in these practices. Using a qualitative descriptive approach with literature review, phenomenological observation, and in-depth interviews with digital preaching practitioners and audiences, this research reveals that broadcasting technology enables wider, faster, and more interactive dissemination of Islamic messages, reaching diverse audience segments. Innovations such as short videos, thematic podcasts, educational animations, and collaborations with Muslim influencers serve as effective strategies to engage the urban youth generation. The shift of dakwah from mosques to cafés signifies a contestation of religious authority, where popular preachers gain new legitimacy in digital public spaces. Furthermore, cultural modification allows dakwah to adapt to urban lifestyles without losing its essential Islamic values. The study concludes that the implementation of broadcasting technology in contemporary dakwah not only transforms the medium of message delivery but also reconstructs preaching strategies and authority, opening opportunities to strengthen religious moderation in the digital era.